2013
DOI: 10.1186/1756-9966-32-41
|View full text |Cite
|
Sign up to set email alerts
|

Let-7b expression determines response to chemotherapy through the regulation of Cyclin D1 in Glioblastoma

Abstract: BackgroundGlioblastoma is the most common type of primary brain tumors. Cisplatin is a commonly used chemotherapeutic agent for Glioblastoma patients. Despite a consistent rate of initial responses, cisplatin treatment often develops chemoresistance, leading to therapeutic failure. Cellular resistance to cisplatin is of great concern and understanding the molecular mechanisms is an utter need.MethodsGlioblastoma cell line U251 cells were exposed to increasing doses of cisplatin for 6 months to establish cispla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 40 publications
0
50
0
Order By: Relevance
“…MiRNAs play important roles in animal development, cell differentiation, and metabolism, and they have been implicated in the sensitivity of tumors to chemotherapy and radiotherapy [14,17,28]. Recently, miRNAs have been shown to be among the critical regulators involved in UM progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MiRNAs play important roles in animal development, cell differentiation, and metabolism, and they have been implicated in the sensitivity of tumors to chemotherapy and radiotherapy [14,17,28]. Recently, miRNAs have been shown to be among the critical regulators involved in UM progression.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer cell lines, let-7 overexpression reduces cell division and inhibits cell cycle progression [21,28,30,31]. Moreover, let-7b overexpression in melanoma cells resulted in significant downregulation of cyclin D1 protein expression by targeting the 3′-UTR of cyclin D1 mRNA [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested that aberrant miR expression levels have been associated with tumor biology, including resistance to various chemotherapeutic agents (9,10). For example, let-7b suppression induces resistance to cisplatin by the upregulation of cyclin D1 in glioblastoma (11). miRs overexpression has also been demonstrated to result in resistance to drugs in colorectal and prostate cancer (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…We previously observed that during this process, cyclin D1 (Ccnd1), a regulator of the G1 phase, is posttranscriptionally regulated by the ATP sensor mTORC1 complex acting through miR-1 and miR-26a (14). In glioblasoma cells (15) and in Respiratory Syncytial Virus (RSV) infected alveolar epithelial cells (16), Ccnd1 is regulated by Let-7 family members. The repression of Ccnd1 protein by miR-1 in mouse myoblasts has also been reported (17).…”
mentioning
confidence: 99%